Sequences of synaptogenesis in the human fetal and neonatal brain by synaptophysin immunocytochemistry - Sarnat, Harvey B. (Frontiers in Cellular Neuroscience, 2023)
Synaptogenesis is the final phase of axonal pathfinding. Its sequences of spatial and temporal development in the immature nervous system are precisely timed and consistent. Synaptophysin, a principal structural glycoprotein of synaptic vesicle membranes regardless of the chemical transmitter substance within, is a reliable means of demonstrating sequences of synaptogenesis in human fetal brain tissue at autopsy and is resistant to postmortem autolysis. Furthermore, synaptophysin molecules are demonstrated during axoplasmic flow before being assembled into membranes in immature axons and also mature axons of neurons with a high metabolic rate. In brain malformations these sequences often are altered both in distribution of synapses and in timing, often delayed but sometimes precocious, with postnatal clinical manifestations such as epilepsy and cognitive development.